Strictly speaking, x^2 + 2x + 4 doesn't have solutions; if you want solutions, you must equate <span>x^2 + 2x + 4 to zero:
</span>x^2 + 2x + 4= 0. "Completing the square" seems to be the easiest way to go here:
rewrite x^2 + 2x + 4 as x^2 + 2x + 1^2 - 1^2 = -4, or
(x+1)^2 = -3
or x+1 =i*(plus or minus sqrt(3))
or x = -1 plus or minus i*sqrt(3)
This problem, like any other quadratic equation, has two roots. Note that the fourth possible answer constitutes one part of the two part solution found above.
Answer:
x < -3
Step-by-step explanation:
Divide both sides by 4. Since 4 is positive, the inequality direction remains the same.
−4x−3> 36/4
Divide 36 by 4 to get 9.
−4x−3>9
Add 3 to both sides.
−4x>9+3
Add 9 and 3 to get 12.
−4x>12
Divide both sides by −4. Since −4 is negative, the inequality direction is changed.
x< 12/-4
Divide 12 by −4 to get −3.
x < -3
Use the pythagoream theorem to check. a^2+b^2=c^2
a=15 b=36 c= 39
225+1296=1521
The equation is true so it is a right triangle.
A.
Because in mathematics, a geometric progression, also known as a geometric sequence, is a sequence of non-zero numbers where each term after the first is found by multiplying the previous one by a fixed, non-zero number called the common ratio.
Answer: 4 cookies per bag
Step-by-step explanation